Capital Structure Affect Asset Structure, Income Volatility, And Financial Flexibility In islamic Industrial Sector Companies - Prasetya, Andre; Santoso, Hadi (ITB AAS INDONESIA Surakarta, 2023)
The capital structure of every company is a critical concern. Capital structure affects a company’s financial status. Financial flexibility, internal company conditions, market conditions, operating leverage, the perspective of lenders and rating agencies, management perspectives, controls,taxes, profitability (lity,afinancialcture, and sales stability) are some of the variables typically taken into account by cperspectivesgement when making decisions about capital structure. The purpose of this study is to ascertain how asset structure, earnings volatility, and financial flexibility impact capitaconsideredmpanies from the consumer products industry sector listed on the Indonesia Stock Exchange. population of this study, and 39 companies were chosen as the sample using a purposive sampling technique. Multiple linear regression analysis utilizing the Eviews program was used in this study. The probability value of the asset structure is 0.0107 0.05, and its positive directional regression coefficient is 0.169937. A positive direction regression coefficient of 0.074237 and a prob value of 0.84246 > 0.05 are both present for earnings volatility. The b-value for financial flexibility is 0.00326 (less than 0.05), and the positive regression coefficient is 0.259236. In conclusion, while earnings volatility has no influence on capital structure, financial flexibility and asset structure variables have beneficial impacts. By examining these aspects, this research is anticipated to help the decision-making process for the growth of a company.